A simulated hospital: an effective teaching tool during the COVID-19 pandemic (2022)
Background: The COVID-19 pandemic has led to the disruption of all sectors of the economy including education. According to UNESCO, over 1.37 million young people, including medical students, were affected by the lockdowns in response to COVID-19 and the subsequent closure of the education system. The main challenge for medical education has consisted in offering clerkships within a biosafety environment. The simulated hospital emerges as a teaching tool that guarantees the development of medical skills in a biosafety environment. Methods: A quasi-experimental design was conducted in a population of 5th-year medical students during their neurology clerkship. The sample comprised two similar groups. The first one received a traditional face-to-face format during 2019, whereas the second group received a mixed virtual and simulation-based clerkship in 2020. At the end of the course, all students in the pandemic group answered a Likert scale survey regarding their satisfaction with the simulated hospital. To evaluate theoretical knowledge acquisition, students of the pandemic and the non-pandemic group were required to perform a mid-term and a final examination. Results: Most of the students considered the simulated hospital a useful addition that should be incorporated into their medicine curriculum regardless of the pandemic. From the results, it is clear that students perceived that exposure to a simulated hospital facilitated their learning process (93.1%) and allowed greater interaction with the teacher compared to a face-to-face environment (77.3%). Although there was a difference in test results, it was not clinically significant. Conclusions: This study shows that a simulated hospital is a highly efficient method to acquire clinical skills in trainees with improvement in medical knowledge and satisfaction evidenced by the Likert scales and comparable results in academic evaluations. The authors experience indicates that exposure to a simulated hospital should be integrated into the curricular milestones of the medical education program regardless of the pandemic.